PENERAPAN MANAJEMEN LALU LINTAS SATU ARAH PADA RUAS JALAN SULTAN AGUNG – SISINGAMANGARAJA – DR.WAHIDIN KOTA SEMARANG UNTUK PEMERATAAN SEBARAN BEBAN LALU LINTAS - Ramadhania Ramanasari; Nurul Qomariyah; Djoko Purwanto; Epf. Eko Yulipriyono (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2014)
Semarang is a capital city of Central Java with high rate of civil growth & mobility. This caused growth of vehicles in Semarang city which keep increasing and has impact in the vehicle’s cumulation on one segment of certain road, such as Dr. Wahidin street and Sultan Agung street . It indicates that on the segment of the road occured a high traffic density that there is a possibility in the upcoming years an increase will happen again. The purpose of the research is to identify the performance of the road’s segment and junction and to find the solution of efficient traffic spread with planned two one way traffic management scenarios. This research begins with literature study and preliminary survey which continued with collecting data through traffic counting, observation, and related measurements. Performance analysis of road’s segments and junctions in existing condition and planned scenario using MKJI 1997. As the result of analysis comparation between existing condition with 2 scenarios which the first scenario (segment of Dr. Wahidin street, Sisingamangaraja street, and Sultan Agung street enforced one way system) and the second scenario (segment of Dr. Wahidin street, Sisingamangaraja street, and Sultan Agung street enforced one way system with contra flow on segment of Dr. Wahidin street and Sultan Agung street) gained that the best scenario is the first scenario. First scenario can decrease the DS of Sultan Agung Street become about 0,21-0,33 and Dr.Wahidin Street about 0,33-0,48. Also after being compared using scoring method, the first scenario got highest score for road’s segment and junctions. So that, scenario 1 can be recommended.